(untitled) (Research, Society and Development, 2021)
According to projections around the world, the elderly population tends to grow in the coming decades. With this growth, the appearance of several pathologies in parallel in a single patient tends to become more common (multimorbidity profile), which is characteristic of this age group. This process, in most cases, is accompanied by the consumption of several medications simultaneously (polypharmacy), which is alarming, considering the physiological changes in the elderly, which lead to greater fragility and propensity to problems related to medications. The Pharmaceutical Assistance is an assertive solution to this problem, through individual clinical monitoring. This is an integrative literature review study, of a qualitative nature, which gathered data dealing with the importance of Pharmaceutical Assistance as a tool for the rational use of medicines in polypharmacy elderly people, having as source the main databases, namely: Pubmed, Scielo, and LILLACS, where the following descriptors were used and combined: Pharmaceutical Care, Polypharmacy, Elderly and Rational Use of Medicines, and for PubMed: Pharmaceutical Care and Polypharmacy and Rational Use of Medicines and Elderly. 79 articles were separated, among which, after exhaustive reading, 17 were selected to compose this work. The literature has shown that the presence of a pharmacist performing Pharmaceutical Assistance interventions in these elderly people is extremely important in improving the quality of life, pharmacotherapy, and in the prevention of adverse events, pointing out the impact and multidimensionality of these interventions as well. bringing improvements about self-care.